2019
DOI: 10.1002/anie.201906293
|View full text |Cite
|
Sign up to set email alerts
|

Flavinium Catalysed Photooxidation: Detection and Characterization of Elusive Peroxyflavinium Intermediates

Abstract: Flavin-based catalysts are photoactive in the visible range whichm akes them useful in biology and chemistry. Herein, we present electrospray-ionization mass-spectrometry detection of short-lived intermediates in photooxidation of toluene catalysed by flavinium ions (Fl + ). Previous studies have shown that photoexcited flavins react with aromates by proton-coupled electron transfer (PCET) on the microsecond time scale.F or Fl + ,P CET leads to FlHC + with the H-atom bound to the N5 position. We show that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 77 publications
1
26
0
1
Order By: Relevance
“…The original Dakin method uses an excess of hydrogen peroxide and sodium hydroxide at elevated temperatures. Interestingly, flavin also catalyzes Dakin oxidation of aromatic aldehydes in the presence of oxygen or hydrogen peroxide as sacrificial oxidants under mild conditions …”
Section: Resultsmentioning
confidence: 99%
“…The original Dakin method uses an excess of hydrogen peroxide and sodium hydroxide at elevated temperatures. Interestingly, flavin also catalyzes Dakin oxidation of aromatic aldehydes in the presence of oxygen or hydrogen peroxide as sacrificial oxidants under mild conditions …”
Section: Resultsmentioning
confidence: 99%
“…A detailed subsequent spectroscopic study revealed that contrary to the reactions in the dark, covalent hydroperoxide binding occurs at the C4a-position with formation of 13 when conducting the reactions with catalyst 11 photochemically (Scheme 12). 22 This observation was rationalized based on a N5blocking effect after initial proton-coupled electron transfer (PCET), which results in N5-protonation. Flavins which contain a substituent in the N1-position, but are not substituted in the N10-position formally belong to the class of alloxazines.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The important role of ion pairing extends in fields like catalysis [5], organic synthesis [6][7][8], and the chemistry of flavonoids [9,10] and radical-induced DNA-strand breaks [11]. These charge-separated reaction intermediates are role of ion pairing extends in fields like catalysis [5], organic synthesis [6][7][8], and the chemistry of flavonoids [9,10] and radical-induced DNA-strand breaks [11]. These charge-separated reaction intermediates are often decisive for the character and efficiency of the follow-up reactions and product formation.…”
Section: Introductionmentioning
confidence: 99%